Electric field control by permittivity functionally graded and superficially non‐linear conductivity materials for DC‐GIS spacer. (3rd March 2022) - Du, Boxue; Dong, Jianan; Liang, Hucheng
Abstract: This paper offers a simulation study on the application of a novel approach to control the electric field around a basin‐type spacer by combining permittivity functionally graded materials ( ε ‐FGM) and superficially non‐linear conductivity materials (SNCM), namely multi‐dimensional functional materials (MDFM). The permittivity distribution of the ε ‐FGM spacer is designed by the iteration optimization algorithm, and the epoxy/SiC composites with 30 and 60 phr doping contents are assigned as the coating materials of two SNCM spacers, namely SNCM30 and SNCM60. The MDFM spacer combines ε ‐FGM in its bulk and SNCM60 on its surface. The electric field regulation effect of each functional spacer is investigated under variable conditions, that is, DC steady state (DC‐steady), DC turn‐on state (DC‐on), DC polarity reversal (DC‐PR), and DC superimposed with switching impulse voltage (DC‐SI). Results show that the applicability of ε ‐FGM and SNCM is limited to transient and stationary conditions, respectively. The MDFM spacer combines the advantages of ε ‐FGM and SNCM for adaptively relaxing the electric field under all the above conditions. It is hoped that this research will be beneficial to the development and application of spacers for the direct current gas‐insulated switchgear (DC‐GIS).